2011
DOI: 10.1136/sti.2010.047407
|View full text |Cite
|
Sign up to set email alerts
|

Which Chinese men who have sex with men miss out on HIV testing?

Abstract: Targeted, culturally appropriate and innovative interventions to increase HIV testing uptake should be a top priority for HIV prevention among MSM in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…As with many countries with a low HIV/AIDS prevalence rate among the general population, however, VCT rates for HIV in China are extremely low. Two studies-a 2006 study in Beijing [33] and a 2008 study in Jinan [29]-found that more than 80% of MSM had not tested for HIV in the past 12 months. Certain demographic patterns were also reported: MSM who were older (at least 35 years old), married, bisexual, or unsure about their sexual identity were more likely to forego HIV testing [29].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…As with many countries with a low HIV/AIDS prevalence rate among the general population, however, VCT rates for HIV in China are extremely low. Two studies-a 2006 study in Beijing [33] and a 2008 study in Jinan [29]-found that more than 80% of MSM had not tested for HIV in the past 12 months. Certain demographic patterns were also reported: MSM who were older (at least 35 years old), married, bisexual, or unsure about their sexual identity were more likely to forego HIV testing [29].…”
Section: Introductionmentioning
confidence: 98%
“…Two studies-a 2006 study in Beijing [33] and a 2008 study in Jinan [29]-found that more than 80% of MSM had not tested for HIV in the past 12 months. Certain demographic patterns were also reported: MSM who were older (at least 35 years old), married, bisexual, or unsure about their sexual identity were more likely to forego HIV testing [29]. Other factors associated with not testing include HIV/AIDS knowledge, accessibility of testing sites, and perceived vulnerability.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 Despite these signs of improvement, however, overall testing rates among MSM in China remain relatively low, with only about half of MSM reporting ever having been tested. 1,4,5 HIV testing serves as a gateway to additional HIV prevention services and to HIV care and treatment if one tests positive. Furthermore, the global AIDS field is shifting toward prevention programming that is contingent on knowing one's HIV status (eg, prevention with positives, test and treat, and chemoprophylaxis).…”
Section: Introductionmentioning
confidence: 99%
“…Likelihood and frequency of testing may be related to demographic characteristics such as sexual orientation, age and ethnicity [14,9,15]; and to fear of positive results, perceived HIV risk, and beliefs about HIV treatment [16,17].…”
Section: Introductionmentioning
confidence: 99%